(untitled) (Journal of the College of Basic Education, 2024)
The study deals with an important topic at the intellectual, academic and religious levels, and it has an important impact on the Islamic arena, which is the concept of reason and the concept of faith and the extent of the connection between these two concepts in the view of the largest philosophical schools known to history, from the pre-Christian era through Western civilizations and Islamic philosophical schools. Coming up with the most important conclusions of this research.